A morte e as perversões em A casa das belas adormecidas , de Yasunari Kawabata - Leonel, Samara (2012)
Although little-studied in the scientific sphere, the subject of sexuality in older individuals has always been topic of literature. In the House of Sleeping Beauties (Nemureru Bijô 1962), the japanese writer Yasunari Kawabata presents an original entertainment house, where elderly men pay for spending the night with beautiful young girls put to sleep through narcotics. One of his last books published presents a series of reflections about love, sex, aging and death, almost in form of essay. The intensity and plasticity of his descriptions and thougts, inspired Gabriel García Márquez to write his book: Memories of my melancholy whores, which has one of Kawabata´s texts as epigram. The aim of this work is to analyse the topics evoked by the novel and distinguished aspects in the treatment of the erotic theme in Japan and in the West, in an effort to map the aspects of this intercultural reception.